Knowledge, Truth, and Interpretation: Revisiting Classical Philosophy in the Digital Age - Sahjad M. Aksan; Wang Jing; Li Na (Yayasan Adra Karima Hubbi, 2026)
Background. The advent of the digital age has drastically transformed the way knowledge is accessed, interpreted, and disseminated. In this context, classical philosophical inquiries into knowledge, truth, and interpretation are being revisited, with new questions emerging about their relevance and application in the age of digital information. Purpose. This research seeks to explore the intersection of classical philosophy and the digital era, examining how timeless philosophical concepts can be adapted to address the challenges and complexities introduced by digital technologies. The main objective of this study is to investigate how classical philosophical perspectives on knowledge, truth, and interpretation can provide valuable insights into understanding the dynamics of the digital age. The study aims to bridge the gap between classical philosophical theories and contemporary digital challenges, exploring how traditional concepts can inform current debates about information, misinformation, and digital ethics. Method. This research employs a qualitative, comparative analysis of classical philosophical texts, including works by Plato, Aristotle, and Kant, in relation to contemporary digital phenomena. A thematic analysis is used to explore the application of these classical ideas to current digital issues, such as the spread of fake news, the ethics of AI, and the role of social media in shaping public opinion. Results. The study finds that classical philosophies on knowledge and truth remain relevant in understanding the digital age, offering frameworks for critically evaluating information and guiding ethical digital practices. Conclusion. The research concludes that revisiting classical philosophy in the digital age provides important insights into managing the challenges of knowledge and truth in a rapidly evolving information landscape.